Fatores sociodemográficos associados à presença de drogas entre os óbitos violentos: estudo seccional no Ceará de 2015 a 2019 - Holanda Júnior, Wanderley Pinheiro de (2022)
The use of chemical substances and violence has been part of human history. The psychotropic drugs affect the central nervous system, modifying psychic activities and they are associated with violent behavior and/or involvement in violent deaths (homicide, suicide, accidental death). The analysis of mortality because of the use of one or multiple chemical agents is of the fundamental importance for the health system, the taking of actions, and the development of specific policies. In this direction, legal medicine and forensic toxicology provide the possibility of unequivocally establishing the cause-and-effect relationship and the involvement of chemical agents and the pattern of mortality associated with illicit drugs. This study explored the association between demographic factors, the presence of licit and illicit drugs and type of legal death (homicide, suicide, accidental death) among individuals with violent deaths in the state of Ceará in the period from 2015 to 2019.This is an sectional, analytical, documentary study using the technique of deterministic and probabilistic linkage performed in the autopsy databases (Integrated Management System - SGI and Forensic Management Software – Galileu System) and results of the toxicological screening tests performed at the Division of Forensic Toxicology of the Forensic Services of the State of Ceará (PEFOCE) from the automated analyzer for biological sample for detection of drugs or drug classes by immunoassay Evidence® Randox. Data were collected and analyzed on deaths according to their legal nature (homicide, suicide, accidental and other - poisoning, work accidents, drowning, falls, electrocution and miscellaneous accidents), presence of illicit substances and class of drugs (outcomes), sex, age, education, profession, marital status, municipality, place of death, type of legal death, location and date of fatal incident, date of examination, type of examination, forensic center (independent variables). Database records were related using the dtalink Stata® program. Prevalences and 95% confidence intervals (95% CI) were calculated for the outcomes. Violent deaths were more incident in males (86.2%), young adults (40.6%), single (66.4%), literate (54.4.%), residents of the metropolitan area of Fortaleza-CE. In 55.6% of the deaths at least one psychoactive substance was detected with a greater participation of benzodiazepines (22.4%) and cocaine (21.7%). The homicides were associated with the detection of cocaine (28.1%) and cannabis (27.1%), occurred among young, single men. Suicides were associated with benzodiazepines (42.6%) and tricyclic antidepressants (15.6%). Suspected deaths were related to the presence of cocaine (28.2%) and tricyclic antidepressants (5.9%). The detection of cocaine (26.5%) and Δ 9 -THC (12.9%) were more prevalent among young adult males and the amphetamine compounds (18.5%) had higher detection among females. It is concluded that psychoactive substances are of important influence in premature death and that it is becoming necessary to investigate the role of toxicological tests in violent deaths in order to establish the relationship between these substances and violent deaths. Further studies are required regarding the casualty of use and the types of legal deaths and their association with the seizure of drugs in the state.